GNEA: A Graph Neural Network with ELM Aggregator for Brain Network Classification. (29th October 2020) - Bi, Xin; Liu, Zhixun; He, Yao; Zhao, Xiangguo; Sun, Yongjiao; Liu, Hao
Abstract : Brain networks provide essential insights into the diagnosis of functional brain disorders, such as Alzheimer's disease (AD). Many machine learning methods have been applied to learn from brain images or networks in Euclidean space. However, it is still challenging to learn complex network structures and the connectivity of brain regions in non-Euclidean space. To address this problem, in this paper, we exploit the study of brain network classification from the perspective of graph learning. We propose an aggregator based on extreme learning machine (ELM) that boosts the aggregation ability and efficiency of graph convolution without iterative tuning. Then, we design a graph neural network named GNEA (Graph Neural Network with ELM Aggregator) for the graph classification task. Extensive experiments are conducted using a real-world AD detection dataset to evaluate and compare the graph learning performances of GNEA and state-of-the-art graph learning methods. The results indicate that GNEA achieves excellent learning performance with the best graph representation ability in brain network classification applications.